Notes on Canon Lury's article - Tracey, Hugh (International Library of African Music, 1956)
Canon Lury expresses in this article (which we reproduce by kind permission of the Editor of The Journal of the Universities' Mission to Central Africa) several opinions which have been gaining ground throughout Africa in recent years. The African Music Society and the staff of the International Library of African Music have found increasing interest in the possibility of bringing scientific knowledge to bear upon this important part of mission work throughout the continent. We hope the publication of this and similar articles in our Journal will stimulate interest in new religious music for Africa, and it is with this end in view that we now add a few editorial notes in extension of what Canon Lury has written.
Keywords: Ethnomusicology; Church music; Gregorian chants; Africa; African Music; Musical Interval; Musical Scale